2012
DOI: 10.1053/j.ajkd.2011.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Kidney Function Decline in the 2 Years Before Initiation of Long-term Dialysis

Abstract: Background Little is known about patterns of kidney function decline leading up to initiation of chronic dialysis. Study Design Retrospective cohort study. Setting and Participants 5,606 VA patients who initiated chronic dialysis in 2001–2003. Predictor: Trajectory of estimated glomerular filtration rate (eGFR) during the two year period before dialysis initiation. Outcomes and Measurements Patient characteristics and care practices before and at the time of dialysis initiation and survival after initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
193
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(211 citation statements)
references
References 25 publications
16
193
0
2
Order By: Relevance
“…The second case report presented above demonstrated the syndrome of rapid onset ESRD, or SORO-ESRD, that is to say, acute yet irreversible renal failure requiring permanent RRT including kidney transplantation where applicable (7)(8)(9)(10). Several other large studies of the trajectories of renal failure to ESRD have confirmed our observations (18)(19)(20). In the more recent nephrology literature, 2011-2012, we have further identified three corroborating new reports that have further substantiated our recent descriptions of the phenomenon of SORO-ESRD (18)(19)(20).…”
Section: Discussionsupporting
confidence: 89%
“…The second case report presented above demonstrated the syndrome of rapid onset ESRD, or SORO-ESRD, that is to say, acute yet irreversible renal failure requiring permanent RRT including kidney transplantation where applicable (7)(8)(9)(10). Several other large studies of the trajectories of renal failure to ESRD have confirmed our observations (18)(19)(20). In the more recent nephrology literature, 2011-2012, we have further identified three corroborating new reports that have further substantiated our recent descriptions of the phenomenon of SORO-ESRD (18)(19)(20).…”
Section: Discussionsupporting
confidence: 89%
“…9 Uncertainty about disease trajectory and prognosis can hamper formulation of future plans and treatment preferences. [10][11][12] Prior studies have evaluated the association of patient characteristics (e.g., comorbid conditions and functional status) 5,13,14 and treatment practices (e.g., early nephrology referral and type of vascular access) 15,16 before and at the time of dialysis initiation with subsequent outcomes. However, many of these analyses did not capture information on clinical circumstances around the time of dialysis initiation.…”
mentioning
confidence: 99%
“…In reality, chronic dialysis is often initiated in the context of acute illness 17,18 and rapid or unexpected loss of renal function. 14 We hypothesized that illness severity around the time of dialysis initiation-as reflected in measures of health care intensity, such as length of hospitalization and use of intensive procedures-might provide information useful for anticipatory guidance and supporting treatment decisions in older adults newly initiated on chronic dialysis. To evaluate this hypothesis, we used data from the U.S. Renal Data System (USRDS), a national registry of ESRD, to identify 416,657 Medicare beneficiaries aged $67 years and describe the intensity of care they experienced around the time of initiation of chronic dialysis and its association with survival and patterns of future healthcare utilization.…”
mentioning
confidence: 99%
“…Few studies have determined the pre-AKI slope, and most instead adjust for the static pre-AKI GFR (see number 1 in Figure 1). One study that identified four different trajectories of kidney function decline before ESRD showed that AKI was more common in those with fast progression to ESRD, yet precipitants such as "hematologic malignancy," "other," and "unknown" were also much more common in fast progressors (22).…”
mentioning
confidence: 99%